2004
DOI: 10.2527/2004.82113237x
|View full text |Cite
|
Sign up to set email alerts
|

Source and level of supplemental protein for growing lambs1

Abstract: Two 3 x 2 factorial growth trials and a companion metabolism trial with 13, 15, or 17% dietary CP (DM basis), with or without 3% of the DM replaced with slowly degraded menhaden fish meal, were conducted to determine if level of dietary protein influences whether slowly degraded protein improves lamb growth and protein use. The growth trials included 32 and 34 pens of two weanling lambs initially weighing 23 to 26 kg and fed for 42 d. The metabolism trial included 12 additional lambs fed in metabolism cages wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
21
3
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 32 publications
7
21
3
1
Order By: Relevance
“…Plasma urea N concentration was unaffected (P = 0.27) by barley processing, but it tended (P = 0.06) to be greater in lambs fed the low dietary RDP compared with those fed the high dietary RDP. Lambs fed high-concentrate diets with N contents comparable to those used in our study (≥27.2 g of N/kg of DM) had similar PUN concentrations (Dabiri and Thonney, 2004;Marini et al, 2004). The greater PUN concentration in lambs fed the low-RDP diet was unexpected, especially considering that these lambs had lower intake of ruminally fermentable N, which would have decreased postabsorptive NH 3 -N supply for hepatic ureagenesis; the reasons for this observation are unclear.…”
Section: Intakes N Balance Urea N Kinetics and Microbial Nonammonimentioning
confidence: 65%
“…Plasma urea N concentration was unaffected (P = 0.27) by barley processing, but it tended (P = 0.06) to be greater in lambs fed the low dietary RDP compared with those fed the high dietary RDP. Lambs fed high-concentrate diets with N contents comparable to those used in our study (≥27.2 g of N/kg of DM) had similar PUN concentrations (Dabiri and Thonney, 2004;Marini et al, 2004). The greater PUN concentration in lambs fed the low-RDP diet was unexpected, especially considering that these lambs had lower intake of ruminally fermentable N, which would have decreased postabsorptive NH 3 -N supply for hepatic ureagenesis; the reasons for this observation are unclear.…”
Section: Intakes N Balance Urea N Kinetics and Microbial Nonammonimentioning
confidence: 65%
“…There was no significant difference in faecal N among the diets with different CP levels . The N excretion through urine apparently showed a positive relationship with the intake (Dabiri and Thonney 2004;Tatsapong et al 2010). Higher CP intake than the optimum or imbalance between energy and protein intake or rapid protein degradation than synthesis leads to more ammonia production in rumen, and the ammonia absorbed into the blood is carried to the liver and converted to urea and excreted via urine N. Hussain et al (2001) observed that energy level had a significant effect on N retention as a percentage of N intake in male buffalo calves.…”
Section: Effect Of Dietary Energy and Protein Concentration On Nutriementioning
confidence: 94%
“…The lower DMI in the R 3 -fed lambs compared to the other lambs may also explained by the lower dietary protein of R 3 . Dabiri & Thonney (2004) reported a lower DMI in lambs receiving 13% protein compared to those received diets containing 15% protein. The CP content of diets is often related positively to DMI (Roffler et al, 1986).…”
Section: Discussionmentioning
confidence: 89%